Stepped Geomorphology Shaped the Phylogeographic Structure of a Widespread Tree Species (Toxicodendron vernicifluum, Anacardiaceae) in East Asia - Wang, Lu; Li, Yao; Noshiro, Shuichi; Suzuki, Mitsuo; Arai, Takahisa; Kobayashi, Kazutaka; Xie, Lei; Zhang, Mingyue; He, Na; Fang, Yanming; Zhang, Feilong (Frontiers in Plant Science, 2022)
Species’ phylogeographic patterns reflect the interplay between landscape features, climatic forces, and evolutionary processes. Here, we used two chloroplast DNA (cpDNA) markers (trnL and trnL-F) to explore the role of stepped geomorphology in shaping the phylogeographic structure of Toxicodendron vernicifluum, an economically important tree species widely distributed in East Asia. The range-wide pattern of sequence variation was analyzed based on a dataset including 357 individuals from China, together with published sequences of 44 individuals mainly from Japan and South Korea. We identified five chloroplast haplotypes based on seven substitutions across the 717-bp alignment. A clear east-west phylogeographic break was recovered according to the stepped landforms of mainland China. The wild trees of the western clade were found to be geographically restricted to the middle ‘step’, which is characterized by high mountains and plateaus, while those of the eastern clade were confined to the low ‘step’, which is mainly made up of hills and plains. Using an isolation-with-migration model, the two major clades were estimated to have diverged during the late Quaternary, suggesting that the cool glacial climate may have caused the ancestral population to retreat to at least two glacial refugia, leading to allopatric divergence in response to long-term geographic isolation. Migration vector analyses based on the outputs of ecological niche models (ENMs) supported a gradual range expansion since the Last Interglacial. Mountain ranges in western China and the East China Sea land bridge were inferred to be dispersal corridors in the western and eastern distributions of T. vernicifluum, respectively. Overall, our study provides solid evidence for the role of stepped geomorphology in shaping the phylogeographic patterns of T. vernicifluum. The resulting east-west genetic discontinuities could persist for a long time, and could occur at a much larger scale than previously reported, extending from subtropical (e.g., the Xuefeng Mountain) to warm-temperate China (e.g., the Taihang Mountain).